2022
DOI: 10.1177/11206721221086244
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of childhood obesity on retrobulbar hemodynamics and retinal microvasculature

Abstract: Objective To evaluate changes in retrobulbar ocular blood flow parameters by using Colour Doppler Imaging (CDI) and changes in foveal microvasculature by using Optical Coherence Tomography Angiography (OCTA) in pediatric obese patients and to compare them with a group of healthy children. Methods Children diagnosed with obesity without hypertension and diabetes (39 subjects, obese group) and age-matched healthy controls (26 subjects, control group) underwent CDI and OCTA imaging. Peak systolic velocity, end-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Changes in retrobulbar blood flow related to obesity during childhood have also been detected by CDI. PSV and EDV of the OA, CRA and SPCA were significantly lower in obese children compared to controls while OCTA imaging did not show retinal microvascular impairment [111]. Lower PSV and EDV values in the CRA and OA in adult patients with obesity were also detected by CDI.…”
Section: Clinical and Scientific Relevance Of CDI For Ocular And Card...mentioning
confidence: 71%
“…Changes in retrobulbar blood flow related to obesity during childhood have also been detected by CDI. PSV and EDV of the OA, CRA and SPCA were significantly lower in obese children compared to controls while OCTA imaging did not show retinal microvascular impairment [111]. Lower PSV and EDV values in the CRA and OA in adult patients with obesity were also detected by CDI.…”
Section: Clinical and Scientific Relevance Of CDI For Ocular And Card...mentioning
confidence: 71%
“…Celik et al found an increase in subfoveal choroidal thickness in obese children. [ 10 ] Younger newly developed obese children in our study may be a reason for it. Obesity is chronic and progressive [ 11 , 12 ], believed to start many years before manifested microvascular dysfunction occurs.…”
Section: Discussionmentioning
confidence: 83%
“…Studies have reported that childhood obesity was associated with retinochoroidal microvascular changes using optical coherence tomography angiography (OCTA) [8][9][10]. However, it is unclear whether estimated associations are mainly driven by persons with long-standing obesity, persons with recently developed obesity, or some combination of both.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Still, differences in OCTA values between obese and healthy children were not demonstrated by all authors ( 57 ), emphasizing the need for further research.…”
Section: Introductionmentioning
confidence: 88%
“…However, it must be emphasized that some studies have not found a significant difference between choroidal and retinal thickness in obese children compared to healthy controls (37,40,57). Further studies to verify changes in CT and MRT are needed in obese juvenile populations.…”
Section: The Association Between Choroidal Thickness and Macular Reti...mentioning
confidence: 97%